2017
DOI: 10.1111/sjos.12281
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Approaches to Estimating the Population Mean with Missing Response

Abstract: We propose new ensemble approaches to estimate the population mean for missing response data with fully observed auxiliary variables. We first compress the working models according to their categories through a weighted average, where the weights are proportional to the square of the least-squares coefficients of model refitting. Based on the compressed values, we develop two ensemble frameworks, under which one is to adjust weights in the inverse probability weighting procedure and the other is built upon an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…To reduce the computational burden, we adopt the approach of Duan and Yin (2017), who proposed to compress the working models through weighted averages. Let…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the computational burden, we adopt the approach of Duan and Yin (2017), who proposed to compress the working models through weighted averages. Let…”
Section: Proposed Methodsmentioning
confidence: 99%
“…To provide additional protection, Han and Wang (2013) introduced the concept of multiple robustness; see also Han (2014aHan ( , 2014bHan ( , 2016aHan ( , 2016b, Chan and Yam (2014), Chen and Haziza (2017) and Duan and Yin (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Using the normalized scores rather than the customary prediction trueU^qitrueη^q ensures that the weighted average lies in the appropriate range; see Duan and Yin (2017). Note that η̂ q is the weighted least square estimator obtained regressing δ i on Û qi based on the responding units.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Suppose that the first model, q 1 ( x i ; γ 1 ) in 𝒞 3 is correctly specified. Then, it can be shown that q̂ i = q 1 ( x i ; γ̂ 1 )+ O p ( n −1/2 ); see Duan and Yin (2017).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Here, if a D .a 1 ; ; a h / is a h-vector, a 2 denotes the column vector .a 2 1 ; ; a 2 h /. Using the normalised scores ensures that the weighted average lies in the appropriate range; see Duan & Yin (2017). The scores O p i and O m i compress respectively the information contained in the J non-response models and the L imputation models.…”
Section: S208mentioning
confidence: 99%